SOSIALISASI DAN EDUKASI PEDULI KESEHATAN MENTAL REMAJA DI MTS ALKHAIRAAT MOUTONG DESA MOUTONG TENGAH KECAMATAN MOUTONG KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH - Tri Setiawati Maulana; Yolanda Ngabito; Novarita Ismail (Journal of Hulonthalo Service Society (JHSS), 2025)
Mts Alkhairaat Moutong adolescents do not fully understand adolescent mental health, so this study aims to increase adolescent knowledge so that they can deal with existing problems with a positive mindset and the mental health of each teenager can be stable. The method used in the socialization and education activities for caring for adolescent mental health was lectures and discussions which were held on July 27 2023 with 30 class 7 students at Mts Alkhairaat Moutong. The results of the implementation of socialization and educational activities that have been carried out show that there are significant mindsets and attitudes from the community and students at MTs Alkhairaat: 1) Ways to prevent adolescent mental health; 2) Implementation of mental health care; 3) Knowing how important it is to care about adolescent mental health. For this reason, this outreach and education activity can produce a young generation who are mentally healthy for the future of the nation, especially students of Mts ALkhairaat Moutong, Middle Moutong Village, Parigi Moutong Regency, from knowing the knowledge about caring for adolescent health.